Simulation of Extreme Arctic Cyclones in IPCC AR5 Experiments - Vavrus, Stephen (2011)
The primary goals of this project are to assess the ability of the current generation of global climate models (GCMs) to simulate extreme Arctic cyclones, and to identify changes in the characteristics of these storms caused by greenhouse-forced climate change to the present. These goals are being addressed through the following questions. First, how realistically does the widely used CCSM4 GCM simulate the observed characteristics of extreme Arctic cyclones, and how sensitive are these events to the horizontal resolution of the model? Second, do other GCMs generate such storms and, if so, are there any common characteristics among models that successfully do so? Third, does the preferred location of these systems and their impact shift as the cyclogenetic baroclinic zone induced by the sea ice margin migrates poleward with time? Fourth, what do these state-of-the-art climate models suggest about changes in the frequency vs. intensity of extreme Arctic cyclones? I am targeting these objectives through a retrospective analysis of the transient 20th century simulations (spanning years 1850-2005) among the GCMs participating in the latest Coupled Model Intercomparison Project (CMIP5). The output from various models is becoming available and eventually should include around 20 GCMs with widely varying resolutions. These simulations will be compared with a new atmospheric reanalysis data set covering almost this entire period (1871-2008) from NOAA's Earth System Research Laboratory: The 20th Century Reanalysis, Version 2. This data set is described in detail by Compo et al. (2010) and provides various atmospheric fields, including sea level pressure, on daily and sub-daily time scales at 2 degrees horizontal resolution. All of this work is being conducted by the PI.